PKM Improving the Competitiveness of Loteng Chips UMKM Through Digital Marketing in Cepik Village, Tabanan, Bali - KURNIAWATI, Ni Putu Ayu Tika; DEWI, A A Istri Krisna Gangga; PUTRA, I Wayan Gde Yogiswara Darma (Indonesia Strategic Sustainability, 2024)
Micro, Small and Medium Enterprises (MSMEs) are increasingly popular in Indonesia and involve mothers, adults, and students. In Cepik Village, Tabanan-Bali, MSMEs sell attic chips, a crunchy and savory snack. The stages of program implementation are as follows :(1) Socialization regarding the importance of attractive and hygienic packaging; (2) Socialization of digital marketing strategies and assistance in creating social media for partner businesses; (3) Socialization of the creation of digital financial reports and training in creating digital financial reports in excel format. Loft chips are fried foods from grated cassava seasoned with salt, garlic, coriander, galangal, and typical fillers such as peanuts or soybeans. This MSME is a typical complementary food to rice in the village. Warmadewa University has the potential to contribute to preserving and developing attic chips MSMEs in Cepik Village by providing facilities, attractive packaging, digital marketing, and training in making digital financial reports. These MSMEs face a lack of understanding of packaging, digital marketing, and digital financial reports.